Sosiaaliturvariippuvuus : sosiaalipummit oleskeluyhteiskunnassa? - Juho Saari (Sosiaaliturvariippuvuus : sosiaalipummit oleskeluyhteiskunnassa?, 2017)
The dependency on social security: Social bums in disengaged society? In Finland, most discussion on the welfare state's condition has focused on stabilizing the public-sector's finances. However, more essential for the future of the welfare state is its' social foundation, meaning people's experiences of fairness, equality and reliability of the society as well as the welfare state's capability of taking care of the most vulnerable groups of people. A functional welfare state combines economic stability with the social foundation. However in the mid 2010s there are cracks in the social foundation of the welfare state . In this book the cracks of welfare state's social foundation are analysed from the perspective of dependency on social security. Especially the Finns' attitudes and political divisions, policies, the length of customership of last-resort social security, the functionality of service and income transfer systems, social segmentation created by breadlines and coping on the last-resort social security are observed. The book is meant for all interested in the condition and future of the welfare state. It is suitable as a textbook in universities and universities of applied sciences. The editor of the book, Juho Saari, is Professor in social and health policy at the University of Tampere and part-time Professor in welfare sociology at the University of Eastern Finland. He has also a docent at the University of Helsinki, at the University of Turku and at the University of Jyväskylä.Painettua kirjaa myy Juvenes Verkkokauppa: https://verkkokauppa.juvenes.fi/tuote/24260/sosiaaliturvariippuvuus-sosiaalipummit-oleskeluyhteiskunnassa. - Suurin osa hyvinvointivaltion tilasta käydystä yhteiskuntapoliittisesta keskustelusta on kohdentunut julkisen talouden vakauttamiseen. Kuitenkin keskeisempää hyvinvointivaltion tulevaisuudelle on sen sosiaalinen perusta, eli ihmisten kokemukset yhteiskunnan reiluudesta, tasa-arvoisuudesta ja luotettavuudesta sekä hyvinvointivaltion kyky kantaa vastuu kaikkein haavoittuvimmassa asemassa olevista ryhmistä. Toimiva hyvinvointivaltio sovittaa yhteen taloudellisen kestävyyden ja sosiaalisen perustan. Kuitenkin 2010-luvun puolivälin hyvinvointivaltion sosiaalisessa perustassa on halkeamia. Tässä teoksessa analysoidaan hyvinvointivaltion sosiaalisen perustan halkeamia ja murroksia sosiaaliturvariippuvuuden näkökulmasta. Erityisesti tarkastelemme siihen liittyviä suomalaisten asenteita ja poliittisia jakolinjoja, politiikkalinjauksia, viimesijaisen turvan asiakkuuksien kestoa, palvelu- ja tulonsiirtojärjestelmien toimivuutta, leipäjonojen luomia yhteiskunnallisia jakolinjoja ja ihmisten selviytymistä viimesijaisella turvalla. Teos on tarkoitettu kaikille hyvinvointivaltion tilasta ja tulevaisuudesta kiinnostuneille. Se soveltuu oppikirjaksi yliopistoihin ja ammattikorkeakouluihin. Teoksen toimittaja Juho Saari on Tampereen yliopiston sosiaali- ja terveyspolitiikan professori ja Itä-Suomen yliopiston hyvinvointisosiologian osa-aikainen professori sekä Helsingin, Turun ja Jyväskylän yliopistojen dosentti